Receiving/declining adjuvant breast cancer treatments and involvement in treatment decision-making. (April 2019) - Kim, Eunjung; Andersen, M. Robyn; Standish, Leanna J.
Highlights: 15.5% of women in INO cohort declined at least one adjutant treatment, compared with 8.8% in UCO cohort. Decliners in INO care are less likely to receive radiotherapy (16.8% vs. 7.2%). Women who used INO care and Decliners, compared with Receivers, tend to be "very involved" in making treatment decisions. No difference was found in participation congruence between Decliners and Receivers in both cohorts. Decliners in INO cohort reported significantly less satisfaction with conventional oncologist than Receivers in INO cohort. Abstract: Objectives: This study compared women who received all recommended breast cancer treatments (Receivers) with those who did not (Decliners). We sought to understand women's integrative naturopathic oncology (INO) use in addition to usual conventional oncology (UCO) use, their involvement in treatment decision-making (TDM), and their satisfaction with healthcare providers. Methods: A secondary analysis was conducted using baseline data from the Breast Cancer Integrative Oncology Study that recruited 427 women from INO clinics (INO cohort) and comparison women from the Cancer Surveillance System Registry who received UCO care (UCO cohort) in Western Washington State. Self-reported data and Registry data were analyzed using descriptive statistics, t-tests, and X2 tests to compare Receivers and Decliners in demographic and disease characteristics, use of INO in addition to UCO care, involvement in TDM, and satisfaction with healthcare providers. Results: Significantly more Decliners were in INO cohort than UCO cohort. Decliners in INO cohort were less likely to receive radiotherapy. Women who used INO care, and Decliners, compared with Receivers, tended to be "very involved" in their TDM. No difference was found in participation congruence, correspondence between preferred and actual involvement in medical TDM, between groups. Decliners in INO cohort reported significantly less satisfaction with their conventional oncologist than Receivers in INO cohort. Conclusions: Decliners of conventional adjuvant therapies were very involved in their TDM and those Decliners who seek INO care were less satisfied with their conventional oncologist; these women may need the most attention to assure they receive the care they need.